Introduction to nanophotonics - Gaponenko, Sergey. V. (Cambridge : Cambridge University Press, 2010)
Nanophotonics is where photonics merges with nanoscience and nanotechnology, and where spatial confinement considerably modifies light propagation and light-matter interaction. The textbook highlights practical issues, material properties and device feasibility, and includes the basic optical properties of metals, semiconductors and dielectrics. Mathematics is kept to a minimum and theoretical issues are reduced to a conceptual level. --from publisher description
Electrons and electromagnetic waves in nanostructures. Basic properties of electromagnetic waves and quantum particles -- Wave optics versus wave mechanics I -- electrons in periodic structures and quantum confinement effects -- Semiconductor nanocrystals (quantum dots) -- Nanoplasmonics I: metal nanoparticles -- Light in periodic structures: photonic crystals -- Light in non-periodic structures -- Photonic circuitry -- Tunneling of light -- Nanoplasmonics II: metal-dielectric nanostructures -- Wave optics versus wave mechanics II -- Light-matter interaction in nanostructures. LIght-matter interaction: introductory quantum electrodynamics -- Density of states effects on optical proecesses in mesoscopic structures -- Light-matter states beyond perturbational approach -- Plasmonic enhancement of secondary radiation.
Includes bibliographical references and indexes.
Keywords: Nanophotonics